"Homeschooling Is Our Protest:" Educational Liberation for African American Homeschooling Families in Philadelphia, PA. Issue 3 (27th May 2019) - Puga, Lisa
ABSTRACT: As increasing numbers of researchers, parents, and youth are rethinking the traditional school system as the default educational option in the United States, homeschooling is not only growing in size but also in philosophical scope and demographic diversity. African Americans particularly have been one of the steadiest-growing homeschooling demographics. Among the few ethnographic accounts of black homeschooling families, youth perceptions tend to be overlooked. This article builds upon scholarship exploring racial injustices in education with new qualitative research: observations and interviews with 15 African American homeschooling families living in Philadelphia. This research reveals a variety of motivations undergirding African American families' homeschooling decisions and perspectives, including commentary from youth homeschoolers. Previous research has critiqued homeschooling as a neoliberal exercise in privatization that entrenches the social reproduction of inequality, or operates as a destabilizing threat to public interest. Yet, findings from this study complicate these assessments by examining the ways African American homeschoolers enmesh themselves within educational reform conversations, some viewing homeschooling as a form of political protest.